Controversy on health-based guidance values for bisphenol A—the need of criteria for studies that serve as a basis for risk assessment - Leist, Marcel; Büttner, Andrea; Diel, Patrick; Eisenbrand, Gerhard; Epe, Bernd; Först, Petra; Grune, Tilman; Haller, Dirk; Heinz, Volker; Hellwig, Michael; Humpf, Hans Ulrich; Jäger, Henry; et al. (Archives of Toxicology, 2024)
Since 2006, the responsible regulatory bodies have proposed five health-based guidance values (HBGV) for bisphenol A (BPA) that differ by a factor of 250,000. This range of HBGVs covers a considerable part of the range from highly toxic to relatively non-toxic substances. As such heterogeneity of regulatory opinions is a challenge not only for scientific risk assessment but also for all stakeholders, the Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) analyzed the reasons for the current discrepancy and used this example to suggest improvements for the process of HBGV recommendations. A key aspect for deriving a HBGV is the selection of appropriate studies that allow the identification of a point of departure (PoD) for risk assessment. In the case of BPA, the HBGV derived in the 2023 EFSA assessment was based on a study that reported an increase of Th17 cells in mice with a benchmark dose lower bound (BMDL40) of 0.53 µg/kg bw/day. However, this study does not comply with several criteria that are important for scientific risk assessment: (1) the selected end-point, Th17 cell frequency in the spleen of mice, is insufficiently understood with respect to health outcomes. (2) It is unclear, by which mechanism BPA may cause an increase in Th17 cell frequency. (3) It is unknown, if an increase of Th17 cell frequency in rodents is comparably observed in humans. (4) Toxicokinetics were not addressed. (5) Neither the raw data nor the experimental protocols are available. A further particularly important criterion (6) is independent data confirmation which is not available in the present case. Previous studies using other readouts did not observe immune-related adverse effects such as inflammation, even at doses orders of magnitude higher than in the Th17 cell-based study. The SKLM not only provides here key criteria for the use of such studies, but also suggests that the use of such a “checklist” requires a careful and comprehensive scientific judgement of each item. It is concluded that the Th17 cell-based study data do not represent an adequate basis for risk assessment of BPA.
CRIS-Team Scopus Importer:2024-06-07